PENGAJARAN BERBASIS ISI PADA PEMBELAJARAN KITAB SYARAH MUKHTASOR JIDDAN - setiadi, agung; Rohmah, Ainur; Kuspiyah, Hastuti Retno (Universitas Sriwijaya, 2020)
This article is aimed to describe the application based on the material in the Bandongan and Sorogan in the learning of the book Syarah Mukhtasor Jiddan in Islamic Boarding School Nurul Huda Sukaraja OKU Timur. A case study with the descriptive method used in conducting this research with observation, interviews and documentation analysis in collecting data. The researcher is positioned as an instrument in this research by following the existing learning process. The data were analyzed by matching theories with applications during the learning process Syarah Mukhtasor Jiddan, the teacher using content based on grammar language material, not using material written in Indonesian but using Arabic text. The CBI model used by teachers consists of additional models.